HYDROXAMATE LIGANDS, SURFACE CHEMISTRY, AND THE MECHANISM OF LIGAND-PROMOTED DISSOLUTION OF GOETHITE [α-FEOOH(S)] - Holmen B.A.; Casey W.H. (My University, 1996)
The rate of goethite dissolution in the presence of acetohydroxamic acid, chosen to be representative of hydroxamate siderophores, was examined in order to understand the cycling of iron in soils. The surface chemistry is surprisingly complicated, with dissolution at pH < 4 caused by reduction of Fe(III) by hydroxylamine that results from surface- or metal-enhanced hydrolysis of the hydroxamate ligand. At pH \gr 4, the rate of dissolution is dominated by the ligand-induced reaction and we propose a mechanism where the rate-controlling step involves replacement of the oxygens near the detaching Fe(III)-monohydroxamate surface complex with water molecules. The adsorbate stoichiometry is given by reaction of oxime and adjacent carbonyl functional groups on the ligand with paired -OH2 and -OH functional groups at monoatomic steps on the goethite surface. Potential factors influencing the rate of iron oxide dissolution by the higher molecular weight siderophores that are produced by iron-deficient microbes include hydrophobic bonding and possible chelation to several Fe(III) sites at the mineral surface.